Comparison of the Effects of Spinal Anaesthesia on Frontal QRS-T Angle in Term and Post-Term Pregnancies Planned for Elective Caesarean Section: A Prospective Study - Ahmet Kaya; Mahmut Alp Karahan; Tugba Bingol Tanriverdi; Alev Esercan; Melike Bostanci Erkmen; Zulkif Tanriverdi (Medicina)
Background and Objectives: Post-term pregnancies are associated with increased risks of perinatal complications. This study aimed to evaluate potential cardiac electrophysiological changes in pregnant women by comparing the QRS duration, interval of corrected QT (QTc), and frontal QRS-T angle [f(QRS-T)] between term and post-term pregnancies. Materials and Methods: In this observational prospective study, 120 pregnant women were enrolled—60 term (37–41 weeks) and 60 post-term (≥42 weeks). All participants underwent standard 12-lead electrocardiography (ECG) and caesarean section with spinal anaesthesia. The QTc interval, QRS duration, and frontal QRS-T angle were measured. Demographic parameters such as age, gestational week, height, and weight were recorded. The SPSS software was used to analyse the data with p < 0.05 as the threshold for significance. Results: Post-operative QTc interval (417.3 ± 20.5 vs. 410.2 ± 14.5, p = 0.032) and f(QRS-T) (28 [16–55] vs. 22 [14–34], p = 0.042) were significantly higher in the post-term group than in the term group. When the change in the f(QRS-T) angle was analysed, there was a significant widening of this angle in the post-term group (from 21 [11–37] to 28 [16–55], p = 0.002). The increased f(QRS-T) angle reflects greater heterogeneity in ventricular depolarisation and repolarisation, which may indicate sub-clinical myocardial stress or altered autonomic regulation in the post-term period. Although no overt arrhythmias were observed, subtle changes in P-wave morphology and QT dispersion were more prevalent in the post-term group. Conclusions: Prolonged QRS duration and an increased f(QRS-T) angle in post-term pregnancies can reflect the underlying changes in cardiac electrophysiology related to prolonged gestation. These ECG parameters may serve as non-invasive indicators of sub-clinical cardiac stress, which could be relevant for anaesthetic risk assessment and perinatal management.